Stretchable Conductive Adhesives with Superior Electrical Stability as Printable Interconnects in Washable Textile Electronics - Ko, Youngpyo; Oh, Jinwoo; Park, Kyung Tae; Kim, Soojin; Huh, Wansoo; Sung, Bong June; Lim, Jung Ah; Lee, Sang-Soo; Kim, Heesuk (American Chemical Society, 2019)
As practical interest in stretchable electronics increases for future applications in wearables, healthcare, and robotics, the demand for electrical interconnects with high electrical conductivity, durability, printability, and adhesion is growing. Despite the high electrical conductivity and stretchability of most previous interconnects, they lack stable conductivity against strain and adhesion to stretchable substrates, leading to a limitation for their practical applications. Herein, we propose a stretchable conductive adhesive consisting of silver particles with carbon nanotube as an auxiliary filler in silicone adhesives. The conductive adhesive exhibits a high initial conductivity of 6450 S cm(-1). They show little change in conductivity over 3000 stretching cycles at 50% strain, currently the highest stability reported for elastic conductors. Based on strong adhesion to stretchable substrates, the gel-free, dry adhesives printed on an elastic bandage for electrocardiography monitoring exhibit an extremely stable performance upon movement of the subject, even after several cycles of detachment-reattachment and machine washing.
Keywords: SILVER NANOPARTICLES; ELASTIC CONDUCTORS; FILMS; FABRICATION; COMPOSITES; RUBBER; LIGHT